Bangabandhu Sheikh Mujib and Education in Emergencies (Teacher’s World: Journal of Education and Research, 2023)
The purpose of this historical review article is to explore how Bangabandhu’s education philosophy contributed to education in emergencies (EiE). The article analyzed historical documents and events to show how Bangabandhu’s speeches and activities were aligned with the idea of the EIE system. The methodology for this study was chosen to apply scientific method to the description and analysis of Banghabandhu’s biography from an educational and philosophical standpoint. Two basic methodological techniques were used: (a) the critical  analysis of all the available documents relating to Banghabandhu; and (b) descriptive details to  show the extent of the influence of various factors on Banghabandhu’s lifestyle and deeds. The findings establish a significant relationship between the educational thoughts of Bangabandhu and the modern concepts, theories, and practices of education in emergencies (EiE). Analyzing Bangabandhu’s educational thoughts and deeds, the findings indicated that Bangabandhu’s philosophy could be the basis of the contemporary idea of EiE. The findings are significant enough to claim Bangabandhu as one of the founders of EiE. Finally, applying strategies  developed by Bangabandhu’s realistic initiatives may have implications in “real-life” situations  involving EIE. In this way, the findings may enable educators, policymakers, and personnel  working in the field of EiE to understand the local contextual perspective of EiE based on  Bangabandhu’s educational principles and thoughts, with policy implications for mitigating the  loss of education for thousands during and after emergencies.Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.7-26